Integrated control strategy for articulated heavy vehicles based on a linear model with real-time parameters. (29th July 2019) - Nie, Zhigen; Gao, Jin; Zhang, Kun
A control strategy for lateral performance improvement of articulated heavy vehicles (AHVs) by integrating active trailer steering and differential braking is presented. A linear model with real-time parameters is adopted in the strategy to achieve precise control for AHVs under the real-time vehicle states and conditions. The strategy is divided into a path following control mode and rollover control mode. A mode switching method is employed by the strategy to achieve good path following and yaw stability under normal working conditions and to avoid vehicle rollover under the limit conditions. Moreover, in order to obtain the optimal control effects for different control objectives and achieve fusion and coordination of multiple subsystems, the genetic particle swarm optimisation algorithm is used to obtain the optimal weight coefficients of the strategy. Experimental verification results indicate that the presented strategy achieves good control for AHVs across a wide range of different operating conditions.